Simultaneous determination of six alkaloids in tobacco and tobacco products by direct analysis of real‐time triple quadrupole mass spectrometry with a modified pretreatment method. Issue 8 (28th February 2020) - Li, Chao; Li, E'xian; Ma, Ming; Liu, Xiuming; You, Junheng; Wu, Yiqin; Jiang, Wei; Liu, Zhihua; Qin, Yunhua
Abstract: In order to determine six alkaloids (mass fraction) of nicotine, nornicotine, myosmine, anatabine, anabasine, and nicotyrine in tobacco and tobacco products quickly, accurately, and simultaneously, a novel method based on direct analysis of real‐time model in situ ionization technique combined tandem mass spectrometry with a modified sample pretreatment was established, in which experimental parameters such as the type and amount of extraction solvent and injection rate were optimized, respectively. The samples of five commercial cigarettes and five kinds of tobacco leaves were analyzed by the established method, and the determined values were compared with those obtained using a gas chromatography with mass spectrometry method: (1) Under optimized conditions (30 mL ultrapure water as extraction solvent and with extraction rate of 0.6 mm/s), analysis could be completed within 10 min. (2) The linear range of the method was 0.002–2000 μg/g with R 2 = 0.9957, the recovery ranged from 86.8 to 105.6%, and the limit of detection and the limit of quantification were 0.004–0.835 μg/g and 0.013–2.787 μg/g, respectively. (3) The relative standard deviation between direct analysis of real‐time method and the gas chromatography with mass spectrometry method was 0.34–8.83%. The established method is rapid, reliable, and suitable for the ultrafast determination of six alkaloids in tobacco and tobacco products.